The difference nanocomposite hardness level using LED photoactivation based on curing period variations - Tatian, Hasiana; Fadil, Moch. Richata; Armilia, Milly (Universitas Padjadjaran, 2011)
Polimerizatian is the critical stage to determine the quality of composites resin, this involves isolated monomer carbon double bonds being converted to an extended network of single bonds. Physical and mechanical properties of composites are influenced by the level of conversion attained during polymerization. An adequate light intensity and light curing time are important to obtain the degree of polymerization. The objective of this study is to evaluate the difference of the hardness nanocomposites which activated by LED LCU based on the variation of curing times. This study is a true experimental research. The samples were made from nanocomposites material with cylinder form of 4 mm in depth, 6 mm in diameter. This samples divided into 3 groups of curing times. Group, I was cured for 20's curing time as a control due to manufactory recommended; Group II was cured for 30's, and Group III was cured for 40's and the hardness (Rebound hardness tester) was determined using Rebound scale (RS) and converted by Mohs scale (MS). There was a very significant level of hardness rate from each group using ANOVA test. The result of the study concludes that there were the differences on the nanocomposites hardness level cured under different curing times 20, 30 and 40 sec. The longer of curing times, the higher level of hardness.